Adolescent and Young Adult Perceptions of Hookah and Little Cigars/Cigarillos: Implications for Risk Messages. Issue 7 (2nd July 2016) - Cornacchione, Jennifer; Wagoner, Kimberly G.; Wiseman, Kimberly D.; Kelley, Dannielle; Noar, Seth M.; Smith, Margaret H.; Sutfin, Erin L.
Abstract : Use of hookah and little cigars/cigarillos (LCCs) is high among adolescents and young adults. Although these products have health effects similar to cigarettes, adolescents and young adults believe them to be safer. This study examined adolescent and young adult perceptions of hookah and LCCs to develop risk messages aimed at discouraging use among users and at-risk nonusers. Ten focus groups with 77 adolescents and young adults were conducted to explore their perceptions about the perceived risks and benefits of hookah and LCC use. Participants were users of other (non-cigarette) tobacco products ( n  = 47) and susceptible nonusers ( n  = 30). Transcripts were coded for emergent themes on participants' perceptions of hookah and LCCs. Participants did not perceive health effects associated with hookah and LCC use to be serious or likely to happen given their infrequency of use and perceptions that they are less harmful than cigarettes. Participants generally had positive associations with smoking hookah and LCCs for several reasons, including that they are used in social gatherings, come in various flavors, and can be used to perform smoke tricks. Because adolescents and young adults underestimate and discount the long-term risks associated with hookah and LCC use, effective messages may be those that focus on the acute/immediate health and cosmetic effects.